Perceptions of convenience, risk and enjoyment in online shopping - Asunmaa, Roosa (2015)
As online shopping is getting more common all the time and competition over customers increases, companies should draw attention to the customer perception of online shopping. Therefore, the present study aims to describe and understand the customer online shopping perception in every stage of the online shopping process. Online shopping has been studied earlier from the viewpoints of the ease of use and the usefulness but as the quickness and easiness of shopping have been found to be factors that motivate customers to use online stores, the customer perception of the convenience of online shop use will be investigated in the present study. In addition to the convenience, the risk and the enjoyment have been found to affect the customers’ willingness to purchase online and both of them are taken into account when revealing the online shopping perception. The present study was conducted as a qualitative research to describe the phenomenon diversely and to increase a practical and theoretical knowledge about the online shopping perception. The data was collected through semistructured interviews and observation. The collected data was analyzed based on the theoretical framework of the present study. The present study finds that the functionality and the content of the site affects the customer perception of convenience, risk and enjoyment. In addition, the personal characteristics of the customer, like the previous experiences of online shopping, have an effect on the perception of online shopping. Different factors of perceived convenience, risk and enjoyment were found in different stages of purchase process. To conclude, the convenience was the most perceived in the pre-stages of purchase since online shops offer functional product search and evaluation tools. The most risk was related to the evaluation, purchase and post-purchase stages due to the non-physicality of online shopping environment. The enjoyment was perceived mostly through the functionality of a page and the easiness of online shopping. The perception of convenience , risk and enjoyment are linked to the overall perception of online shopping and customer behavior in online shopping environment.